2022
DOI: 10.1186/s10086-022-02033-6
|View full text |Cite
|
Sign up to set email alerts
|

Marker-free genome editing in the edible mushroom, Pleurotus ostreatus, using transient expression of genes required for CRISPR/Cas9 and for selection

Abstract: In a previous study, we reported a transient transformation system using repeated screening for hygromycin B (Hyg) resistance in the basidiomycete Ceriporiopsis subvermispora. In the present study, by combining this technique with CRISPR/Cas9, we demonstrated successful marker-free genome editing in Pleurotus ostreatus, which is one of the most economically important cultivated mushrooms as well as a model white-rot fungus. At first, transformant selection mediated by the transient expression of marker genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It can confer different levels of drug resistance depending on its expression levels, allowing transient drug-resistant transformants to be selected under suitable screening conditions. Using the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) genome editing system in P. ostreatus , Koshi et al ( 2022 , also see below) demonstrated that a plasmid expressing Cas9 and guide RNA (gRNA) allows successful genome editing through transient expression of these genes as well as hygromycin resistance markers used for temporal screening of the transformant. In the future, the transient expression of introduced genes could be used for various objectives, such as marker recycling.…”
Section: Genetic Toolbox For P Ostreatusmentioning
confidence: 99%
See 1 more Smart Citation
“…It can confer different levels of drug resistance depending on its expression levels, allowing transient drug-resistant transformants to be selected under suitable screening conditions. Using the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) genome editing system in P. ostreatus , Koshi et al ( 2022 , also see below) demonstrated that a plasmid expressing Cas9 and guide RNA (gRNA) allows successful genome editing through transient expression of these genes as well as hygromycin resistance markers used for temporal screening of the transformant. In the future, the transient expression of introduced genes could be used for various objectives, such as marker recycling.…”
Section: Genetic Toolbox For P Ostreatusmentioning
confidence: 99%
“…Recently, the DNA-mediated CRISPR/Cas9 was reported in agaricomycetes, such as C. cinerea (Sugano et al 2017 ), G. lingzhi (Qin et al 2017 ), G. lucidum (Qin et al 2017 ; Liu et al 2020 ), P. ostreatus (Boontawon et al 2021a ; Xu et al 2022 ; Yamasaki et al 2022 ; Koshi et al 2022 ), P. eryngii (Wang et al 2021 ), L. edodes (Moon et al 2021 ; Kamiya et al 2023 ), Flammulina filiformis (Liu et al 2022a ), G. subvermispora (Nakazawa et al 2022 ), and Agaricus bisporus (Choi et al 2023 ) (Table 1 ). In addition to the expected small insertion or deletion mutations at the target site, integration of introduced DNA fragments has been frequently observed in P. osteatus (Yamasaki et al 2022 ; Koshi et al 2022 ). This could be a result of high selection pressure for hygromycin resistance (Yamasaki et al 2022 ; Koshi et al 2022 ) but similar phenomena may occur in many other cases.…”
Section: Genetic Toolbox For P Ostreatusmentioning
confidence: 99%
“…Next, we examined whether a mutation was introduced into each of the four genes (vp2, vp3, mnp3, or mnp6) in each transformant using genomic PCR experiments. Our previous studies showed that the introduced plasmid(s) were often integrated at the target site of sgRNA in some of the P. ostreatus mutants obtained from the pCcPef3-126-based CRISPR/Cas9 (Boontawon, Nakazawa, Horii, et al, 2021;Boontawon, Nakazawa, Inoue, et al, 2021;Koshi et al, 2022;Yamasaki et al, 2022). This usually caused insufficient amplification from the mutants with large insertions due to the requirement of a longer extension time than the fragment amplified from the parental control strain.…”
Section: Isolation and Characterization Of Vp2/vp3/ Mnp3/mnp6 Quadrup...mentioning
confidence: 99%
“…These four different plasmids were introduced into PC9 × # 64 to obtain mutants with low basidiospore production ability, so as to develop an efficient and rapid molecular breeding method for cultivated mushrooms. Koshi et al ( 2022 ) achieved marker-free genome editing for the first time by transiently expressing Cas9, sgRNA, and hph in P. ostreatus . The gene of fcy1 was edited by transiently expressing Cas9, sgRNA, and hph , and strains with 5-fluorocytosine resistance and hyg sensitivity were isolated.…”
Section: Application Progress Of Crispr/cas9 In Edible Fungimentioning
confidence: 99%